Finding reward in cost: A study of marriage satisfaction in Ta'aruf from the perspective of social exchange theory - Ratriastu Ruciswandaru; Evelyn Evelyn; Muhammad Ahyar Hamka; Yudiana Ratnasari (International Journal Labs, 2025)
This study focuses on the experiences of married women through the ta'aruf process to understand how they interpret religious, social, and emotional roles in building marital satisfaction and how they manage the challenges that arise in domestic life. The data were collected through semi-structured interviews through Zoom Meeting. Data were analyzed thematically through transcription, grouping based on reward and cost dimensions, and interpretation of the meaning of respondents' experiences to identify general patterns in the dynamics of social exchange during marriage. The findings show that religion plays a key role in marriage-related decision-making among respondents, namely internal factors (attraction and relationship with the partner), external factors (family, socio-economic, or cultural), and belief factors (religious values). This study also emphasizes the concept that conflict can be perceived simultaneously as an interpersonal cost to the partner, as well as a reward in the spiritual dimension. These findings provide new insights into how couples manage marital challenges in a religious context.